2010
DOI: 10.1038/nrm2941
|View full text |Cite|
|
Sign up to set email alerts
|

The HSP70 chaperone machinery: J proteins as drivers of functional specificity

Abstract: Hsp70s, ubiquitous molecular chaperones, function in a myriad of biological processes, modulating polypeptides' folding, degradation and translocation across membranes, as well as protein-protein interactions. This multitude of roles is not easily reconciled with the near conformity of biochemical activity of Hsp70s, an ATP-dependent client protein binding/release cycle. Much of the functional diversity of Hsp70s is driven by a diverse class of cofactors, Jproteins (also called Hsp40s). Often, multiple J-prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
1,746
1
35

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,506 publications
(1,818 citation statements)
references
References 142 publications
36
1,746
1
35
Order By: Relevance
“…HSPs are classified in six sub groups: HSPA (HSP70), HSPB (small HSPs), HSPC (HSP90), HSPD and HSPE (chaperonin families HSP60 and HSP10, respectively), HSPH (HSP110), and DNAJ (HSP40) 29 . Each subgroup comprises several family members and cofactors with distinct and/or overlapping functions, which are localized in various cellular com partments 30,31 . Members can be constitutively expressed or are induced by many different intrinsic or extrin sic stressors 30,[32][33][34] .…”
Section: The Proteostasis Network Componentsmentioning
confidence: 99%
“…HSPs are classified in six sub groups: HSPA (HSP70), HSPB (small HSPs), HSPC (HSP90), HSPD and HSPE (chaperonin families HSP60 and HSP10, respectively), HSPH (HSP110), and DNAJ (HSP40) 29 . Each subgroup comprises several family members and cofactors with distinct and/or overlapping functions, which are localized in various cellular com partments 30,31 . Members can be constitutively expressed or are induced by many different intrinsic or extrin sic stressors 30,[32][33][34] .…”
Section: The Proteostasis Network Componentsmentioning
confidence: 99%
“…Consequently, cells possess a variety of different Hsp40 molecules with different substrate binding properties which further broadens the activity spectrum of Hsp70 (Kampinga and Craig, 2010). In addition to Hsp40, NEFs play a pivotal role in the functional cycle of Hsp70.…”
Section: Ii41121 the Hsp70 Chaperone Systemmentioning
confidence: 99%
“…It has been suggested that different Hsp40s, due to their substrate recognition ability, may provide substrate specificity to Hsp70 (Qiu et al, 2006). The Hsp40 members have in common a conserved J-domain and are subdivided into three distinct groups (DnaJA, DnaJB and DnaJC) based on the presence of certain structural motifs (Cheetham and Caplan, 1998;Kampinga and Craig, 2010). However, among these different Hsp40 members, only DnaJB1 has been studied in detail.…”
Section: Vi8 Role Of Dnajb1 In the Degradation Of Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…They also have known functions in protein translocation across biological membranes and dissolution of aggregates 12. Nascent and newly synthesized polypeptides are bound by HSP70, initially stabilising the unfolded state; upon subsequent release into solution they then reach their native folded state 9.…”
Section: Introductionmentioning
confidence: 99%